Pneumocistis jiroveci Pneumonia in an AIDS-presenter Host: Missing the Target in the COVID-19 Epidemic - A, Vergori; I, Mastrorosa; C, Pinnetti; M, Camici; F, Di Stefano; A, Mastrobattista; A, Vulcano; B, Bartolini; G, Granata; S, Topino; et al. (Archives of Clinical and Medical Case Reports, 2020)
We report a case of a previously healthy man admitted with the suspicion of a COVID-19 pneumonia during the Italian pandemic. After 9 days the patient was diagnosed with a new HIV-1 infection with an etiologically confirmed Pneumocistis jiroveci pneumonia (PJP). With this description we would like to highlight the similarities of COVID-19 with PJP and that clinicians should consider other causative agents and that HIV testing should always be offered. <gdiv></gdiv>